USE OF ARTIFICIAL INTELLIGENCE TECHNIQUES FOR PROGNOSTICS: NEW APPLICATION OF ROUGH SETS - Zalewski, Janusz; Wojcik, Zbigniew (International Journal of Computing, 2014)
The objective of this paper is to set the context for the potential application of rough sets in prognostics. Prognostics is a field of engineering, which deals with predicting faults and failures in technical systems. Engineering solutions to respective problems embrace the use of multiple Artificial Intelligence (AI) techniques. The authors, first, review selected AI techniques used in prognostics and then propose the application of rough sets to build the system health prognostication model.